2011
DOI: 10.1111/j.1469-8986.2011.01213.x
|View full text |Cite
|
Sign up to set email alerts
|

Volitional saccades and attentional mechanisms in schizophrenia patients and healthy control subjects

Abstract: Schizophrenia (SZ) patients showed increased volitional saccade latencies, suggesting deficient volitional initiation of action. Yet increased volitional saccade latencies may also result from deficits in attention shifts. To dissociate attention shifting and saccade initiation, we asked 25 SZ patients and 25 healthy subjects to make saccades toward newly appearing (onset) targets and toward the loci of disappearing (offset) targets. Similar onsets and offsets were also used as attention cues in a Posner-type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 39 publications
(66 reference statements)
0
13
0
Order By: Relevance
“…However, onset/offset differences are again smaller than the effects observed with the MDOR task. For a prosaccade task, Pratt and Trottier ( 2005 ) reported this difference (the “cost” of the saccade target being an offset) to be of the order of 50–90 ms. Reuter et al ( 2011 ) reported differences of a similar magnitude. In a more recent study, Reuter et al ( 2016 ) reported data for synchronous and overlap prosaccade tasks in control participants for a clinical study, in which the offset/onset difference was smaller; differences of 37 and 17 ms were observed.…”
Section: Discussionmentioning
confidence: 76%
“…However, onset/offset differences are again smaller than the effects observed with the MDOR task. For a prosaccade task, Pratt and Trottier ( 2005 ) reported this difference (the “cost” of the saccade target being an offset) to be of the order of 50–90 ms. Reuter et al ( 2011 ) reported differences of a similar magnitude. In a more recent study, Reuter et al ( 2016 ) reported data for synchronous and overlap prosaccade tasks in control participants for a clinical study, in which the offset/onset difference was smaller; differences of 37 and 17 ms were observed.…”
Section: Discussionmentioning
confidence: 76%
“…Additionally, the structures and connections underlying oculomotor neurophysiology have been well characterized (Gaymard et al, 1998;Leigh and Zee, 1999;Munoz and Everling, 2004;Munoz et al, 2000). Eye movement tasks have provided powerful insight into neurological dysfunction in clinical disorders such as Parkinson's disease (Terao et al, 2011), attention-deficit/ hyperactivity disorder (ADHD) (Mahone et al, 2009) and schizophrenia (Reuter et al, 2011). For example, deficits in eye movement control are measurable in both children and adults with ADHD, and are consistent with frontostriatal pathophysiology (Munoz et al, 2003).…”
mentioning
confidence: 96%
“…With respect to within‐subject variability of saccadic latencies, our study might contribute to the question of diagnostic specificity of oculomotor dysfunctions. In schizophrenia patients, a similar pattern of results emerges in terms of saccade latencies: Prosaccade latencies are considered unaffected (Gooding & Basso, ), whereas most (e.g., Bender et al, ; Reuter, Elsner, Möllers, & Kathmann, ; Reuter, Jäger, Bottlender, & Kathmann, ) but not all (Reuter et al, ) studies on simple volitional saccade latencies found increased latencies. Looking at within‐subject variability of saccade latencies, a different pattern appears.…”
Section: Discussionmentioning
confidence: 79%